2017
DOI: 10.1523/jneurosci.3209-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Cognitive Dissonance (Revised): An EEG Study

Abstract: Cognitive dissonance theory suggests that our preferences are modulated by the mere act of choosing. A choice between two similarly valued alternatives creates psychological tension (cognitive dissonance) that is reduced by a postdecisional reevaluation of the alternatives. We measured EEG of human subjects during rest and free-choice paradigm. Our study demonstrates that choices associated with stronger cognitive dissonance trigger a larger negative frontocentral evoked response similar to error-related negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 66 publications
2
46
0
Order By: Relevance
“…Overall, these findings are consistent with theories that posit that the brain continuously recalibrates generative (forward) models to maintain self-consistency (e.g., K J Friston et al 2010), and offers a neuro-computationally plausible implementation to resolve cognitive conflicts, which can sometimes appear as irrational behaviors, such as in post-choice re-evaluation of alternatives (Coppin et al 2010;Izuma et al 2010;Colosio et al 2017;Otten, Seth, and Pinto 2017).…”
Section: Introductionsupporting
confidence: 83%
“…Overall, these findings are consistent with theories that posit that the brain continuously recalibrates generative (forward) models to maintain self-consistency (e.g., K J Friston et al 2010), and offers a neuro-computationally plausible implementation to resolve cognitive conflicts, which can sometimes appear as irrational behaviors, such as in post-choice re-evaluation of alternatives (Coppin et al 2010;Izuma et al 2010;Colosio et al 2017;Otten, Seth, and Pinto 2017).…”
Section: Introductionsupporting
confidence: 83%
“…Although compatible with post-choice CIPC, such causal effects can be due to the post-choice disturbance of value representations that resulted from intrachoice CIPC. On the other hand, many recent studies show that brain activity measured during the choice process is predictive of the magnitude of CIPC (Colosio et al, 2017;Jarcho, Berkman, & Lieberman, 2010;Kitayama et al, 2013;van Veen et al, 2009, Voigt et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent neuroimaging evidence suggests that, in the context of typical free-choice paradigms, preference changes occur during the decision, not after it (Jarcho, Berkman, & Lieberman, 2010;Colosio et al, 2017). Recall that people are reluctant to make a choice that they are not confident about (De Martino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By subtracting the mean second rating (rating II) from the mean initial rating (rating I), it is possible to measure the choice-induced preference change. Because Brehm's (1956) free-choice paradigm studies have repeatedly demonstrated that the mere act of choosing between two equally attractive alternatives induces preference change, preferences for the chosen items increases, while preferences for the rejected items decreases (Brehm, 1956;Colosio, Shestakova, Nikulin, Blagovechtchenski, & Klucharev, 2017;Festinger, 1957;Gerard & White, 1983;Izuma et al, 2010). Thus, contrary to normative economic theory, individuals not only behave in accordance with their preferences but also change their preferences to match their previous choices and behavior.…”
Section: Introductionmentioning
confidence: 97%